ANALISIS AKAR RESISTENSI MASYARAKAT DESA SENGANAN, KABUPATEN TABANAN DALAM PEMILIHAN CALON KEPALA DAERAH TAHUN 2015 - Anggraeni, Gusti Ayu Putu Dewi; Erawan, Drs. I Ketut Putra; Bandiyah, S.Fil., MA, Bandiyah (Jurnal Nawala Politika; 2016, 2016)
ABSTRACT The phenomenon of resistance by the senganan of the prospective head region in the election  outright by 2015, became the basis of what's interesting about this research to show how the action of rejection can make the benchmark for other villages in the fight to make choices in the implementation of the election. As a step a theoretical, this study uses the theory of James C. Scoot the resisten and the mobilization, in doing analysis on the results of research. The method used in this study is the method of qualitative descriptive, while the techniques of collecting data through interviews, chat with a lot of people, and analysis of documents. The findings in the field indicate the presence of the dominance of the prospective head region to influence the vote in the implementation of the election in a way of the village chief to influence people in the award of a potential partner number.. Furthermore, resistance.the villagers senganan by using two ways namely resistance and resistance in disguise. Impilikasi the theoretical to show that the theory of domination and the mobilization of society affects the resistance of the village senganan in the implementation of the election outright by 2015. Keywords: Resistance, Village Senganan, Election